2003
DOI: 10.1002/anie.200350961
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibers of 1,3‐Diphenyl‐2‐pyrazoline Induced by Cetyltrimethylammonium Bromide Micelles

Abstract: A self‐inducing template‐growth approach to the production of nanofibers of 1,3‐diphenyl‐2‐pyrazoline (DP) in the presence of cetyltrimethylammonium bromide (CTAB) in an aqueous phase is discussed (see picture). Not only the surfactant CTAB molecules assume the role of surface‐active colloidal stabilizers; but also the rodlike CTAB micelles, which are induced by DP molecules dissolved in spherical CTAB micelles, further direct the growth of cylindrical DP nanofibers like templates. It is found that the crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(103 citation statements)
references
References 27 publications
6
96
0
1
Order By: Relevance
“…This method has been used successfully in the literature to generate nanofibers from different molecules. For instance, the formation of nanowire crystals has been reported for 1,3-diphenyl-2-pyrazoline (26) (Fu et al, 2003) (Fig. 8).…”
Section: Nanofibers Made Of Low-molecular-weight Molecules Without Apmentioning
confidence: 88%
“…This method has been used successfully in the literature to generate nanofibers from different molecules. For instance, the formation of nanowire crystals has been reported for 1,3-diphenyl-2-pyrazoline (26) (Fu et al, 2003) (Fig. 8).…”
Section: Nanofibers Made Of Low-molecular-weight Molecules Without Apmentioning
confidence: 88%
“…Yao and coworkers reported nanofibers of 1,3-diphenyl-2-pyrazoline (DP) induced by CTAB micelles. [140] Figure 5A shows the SEM morphology of the prepared DP nanofibers. It is found that the shape and size of the obtained nanostructures can be controlled by changing the molar ratio of DP to CTAB.…”
Section: Template Method: Soft Templatesmentioning
confidence: 99%
“…The extensively used templates include surfactant micelles and aggregates [144]. Surfactant molecules such as hexadecyltrimethylammonium bromide (CTAB) [145], sodium dodecylsulfate (SDS) [146], a triblock copolymer and (PEO) 20 -(PPO) 70 -(PEO) 20 (Pluronic P123) have been explored as soft templates, acting as the segregates for nanostructures. Other useful soft templates for the synthesis of one-dimensional nanostructures include amphiphilic molecules, copolymers [147], liquid crystals, polymer nanofibres and self-assembled monolayers, biological molecules and macromolecular self-organized structures.…”
Section: Introductionmentioning
confidence: 99%